Evaluation of Gene Expression Level of miRNA-29c, miRNA-125, miRNA-141, miRNA-145 and miRNA-205 as Predisposing Factors for Transitional Cell Carcinoma-Bladder Cancer in Iraqi Patients - Abbas, Sura Mouaid; Dhahi, Maysaa Abdul Razzaq; Muhammad, Saif Hammed (Iraqi Journal of Science, 2023)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression post-transcriptionally. Transitional cell carcinoma(TCC) of the bladder Cancer (C) account 95 percent of bladder malignancies, with males having a greater prevalence than females. The current study sought to determine whether there is a link between miRNA-29c, miRNA-125, miRNA-141, miRNA-145 and miRNA205 expression levels and TCC/BC risk in Iraqi bladder cancer patients. In the current prospective cross-sectional investigation, 149 samples were collected (95 urine and 54 tissue biopsies). From November 2018 to August 2019, 37/95 urine samples were randomly taken from healthy persons. Total RNA was extracted from tissue and urine samples, and then converted to cDNA via reverse transcription. Quantitate Real-Time-PCR was done using specific primers for quantification of gene expression level of the studied miRNAs. The results showed that 32/49 (65%) patients had non-muscles invasive bladder cancer (stage T1), while 17/49 (35%) patients had muscles invasive bladder cancer (stage T2-T4). Fold change in miRNA-125 expression level showed highly significant differences between non-muscles invasive bladder cancer (T1) and muscles invasion bladder cancer (T2-T4) in both urine and tissue samples biopsies using Chi-square test at p ≤ 0.01. Whereas miR-29c, miR-141, miR-145 and miR-205 showed no significant differences at p > 0.05 between muscles invasive bladder cancer (T1) and muscles invasive bladder cancer (T2-T4) in both urine and tissue biopsies samples. Thus, miR-125 can be associated with the development of invasive stages of TCC-BC as there is an increase in miR-125 expression level in the urine of patients during the final stage of cancer.Hence, this gene could be considered a good predictor in advanced stages of bladder cancer.